2010
DOI: 10.1111/j.1365-2230.2009.03419.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical insulin on cutaneous wound healing in rats with or without acute diabetes

Abstract: This study revealed that topical insulin application to cutaneous wounds accelerates wound healing in rats with or without acute diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 18 publications
7
54
0
3
Order By: Relevance
“…Organization of collagen fibers was greater in the diabetic group treated with topical insulin (DI group) than in the other groups. Our results are consistent with those of other studies that have shown that topical insulin enhances wound healing by increasing collagen deposition (Apikoglu-Rabus et al, 2010;Madibally et al, 2003).…”
Section: Discussionsupporting
confidence: 95%
“…Organization of collagen fibers was greater in the diabetic group treated with topical insulin (DI group) than in the other groups. Our results are consistent with those of other studies that have shown that topical insulin enhances wound healing by increasing collagen deposition (Apikoglu-Rabus et al, 2010;Madibally et al, 2003).…”
Section: Discussionsupporting
confidence: 95%
“…Our results suggest a characteristic spatial distribution and evolution of perfusion changes that may be exploited to influence local or topical delivery strategies of therapeutic agents such insulin or silver nanoparticles [45, 46], and help understand the regional biodistribution of systemically administered drugs. In vivo LSCI-based flow and vascularization metrics could also provide a non-invasive indication of the degree of wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the insulin diffuses through the interior of the fibers to its surface and across the boundary layer, reaching the external medium. Regularity in insulin release in vitro is promising for obtaining an artificial insulin depot with controllable and continued activity that may be used topically for better healing of diabetic' wounds [34] or for transdermal and subcutaneous insulin delivery [35].…”
Section: Kinetics Of Insulin Release From Dac-insulin Complexmentioning
confidence: 99%